What and Where on Earth Is Waqwaq? - Toorawa, Shawkat M. (Journal of Abbasid Studies, 2023)
For well over a century, Indian Ocean Arabists, using primarily linguistic (and biological) arguments, have posited that Waqwaq is one place or another, one life-form or another. It is now Madagascar, now Sumatra; now a milkweed, now a pandanus; now a bird, now a woman-fruit. It is now a tree, now an island … I myself have not been immune to this need to identify, categorize, classify, locate, and domesticate Waqwaq. The impulse is a dangerous one: it arises out of a notion implicit in the colonial and philological enterprise that to be able to name something, to know how it got its name, and to put it on one’s map, is the better to be able to control it. Recent scholarship has been less constrained by potential philological and interpretive tyrannies and Waqwaq has accordingly benefited from re-sitings and re-readings. In this paper, I ask: What are the roots of Waqwaq and what routes has it taken as it traveled from the Abbasid court to China, from Japan to the Mascarenes, from India to the Philippines, from Istanbul to the New World, and even to Hell (and back).